Common Obesity Syndromes in Childhood - Hatice Mutlu Albayrak; Beray Selver Eklioğlu (Güncel Pediatri, 2016)
Syndromic obesity occurs with different genetic or chromosomal disorders. Obesity is accompanied by dysmorphic features, mental retardation and developmental abnormalities. Prader-Willi syndrome, Bardet-Biedl syndrome and Alström syndrome are the most commonly encountered obesity syndromes, in clinical practice. Prader-Willi syndrome is an obesity syndrome, characterized by hypotonia, hyperphagia, hypogonadism and short stature due to genomic imprinting defect. Bardet-Biedl syndrome is a genetically heterogeneous ciliopathy syndrome caused by autosomal recessive genes, characterized by retinal dystrophy, truncal obesity, postaxial polydactyly, learning difficulties, renal anomalies, and hypogonadotropic hypogonadism only in males, Alström syndrome is an autosomal recessive syndrome, characterized by progressive cone-rod dystrophy, obesity and sensorineural hearing loss accompanied by multi-organ involvement. If exogenous and monogenic obesity is excluded, not only hormonal evaluation but also additional dysmorphic features, ophthalmic, dental, cardiac, renal, and neurological systems should also be evaluated to approach syndromic obesity. Genetic diagnostic analysis should be utilized for confirming the diagnosis and providing genetic counseling to families.